グリーンランド北西部ボードウィンフィヨルドにおける係留観測 - 深町, 康; 漢那, 直也; 杉山, 慎; 大橋, 良彦; 榊原, 大貴; 野村, 大樹; Yasushi, Fukamachi; Naoya, Kanna; Shin, Sugiyama; Yoshihiko, Ohashi; Daiki, Sakakibara; Daiki, Nomura (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object